Green Open Space Governance Strategy Against City Development in East Jakarta Mayor Perspective of Law Number 26 of 2007 concerning Spatial Planning - Pamungkas Alukman Nulhakim; Siti Ngainnur Rohmah; Abu Tamrin; Mufidah Mufidah (JOURNAL of LEGAL RESEARCH, 2022)
The existence of Law Number 26 of 2007 concerning spatial planning is a shared hope, both for the local government and the community in East Jakarta Municipality. Urban problems arise due to unclear urban spatial planning, as well as inconsistencies in environmental management. The purpose of this study is to explain the importance of managing urban spatial planning as a strategy for designing and developing environmentally friendly areas in East Jakarta Municipality based on Law Number 26 of 2007 concerning Spatial Planning. The research method used is qualitative with a normative and empirical juridical approach. The results of the study found that one of the benchmarks for the application of the Green City concept is the existence of Green Open Space (RTH) in urban areas. Green Open Space in a city must meet a minimum area of 30% of the total land area, with a composition of 20% public green open space and 10% private green open space (Law No. 26 of 2007).